(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Practice demonstrates that public health emergencies of particular severity have the capacity to drive reforms in global health governance. This study examines how recent emergencies, such as the Ebola outbreak in West Africa and the COVID-19 pandemic, have impacted governance systems, with specific reference to the process of health securitization and the revision of the 2005 International Health Regulations.